2018
DOI: 10.1055/s-0038-1672135
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Osteogenesis Imperfecta Variants of Uncertain Significance in the Context of Physical Abuse: A Case Series

Abstract: Unexplained childhood fracture(s) warrant consideration of physical abuse and osteogenesis imperfecta (OI). Genetic OI testing may identify “variants of unknown significance (VUS).” Interpretation of VUS in context of potential abuse may have protective, criminal, and medical impacts. This case series explores practices regarding clinicians' interpretation of VUS during child abuse evaluations. Variability was noted regarding factors considered for interpreting clinical significance. Based on these cases, reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…We need to address racism and implicit bias in reporting as well as improve our identification of child abuse injuries in the office and the hospital (Greiner et al, 2013; Kennedy et al, 2020; Palusci et al, 2019; Palusci & Botash, 2021). We need to better understand genetic and epigenetic changes and how to intervene in varied settings (LeBlanc et al, 2019; Canter, Rao, Palusci, et al, 2019). Our preliminary review of medical research publications showed definite, albeit sluggish, growth in the number of publications over time (Palusci & Perfetto, 2019), and it is promising that there has been a call for a research agenda for and increased funding in these areas, including studies of longterm effects (Lindberg et al, 2017; CDC, 2021; Recover, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We need to address racism and implicit bias in reporting as well as improve our identification of child abuse injuries in the office and the hospital (Greiner et al, 2013; Kennedy et al, 2020; Palusci et al, 2019; Palusci & Botash, 2021). We need to better understand genetic and epigenetic changes and how to intervene in varied settings (LeBlanc et al, 2019; Canter, Rao, Palusci, et al, 2019). Our preliminary review of medical research publications showed definite, albeit sluggish, growth in the number of publications over time (Palusci & Perfetto, 2019), and it is promising that there has been a call for a research agenda for and increased funding in these areas, including studies of longterm effects (Lindberg et al, 2017; CDC, 2021; Recover, 2021).…”
Section: Discussionmentioning
confidence: 99%